Pre-metastatic Niche Formation in Different Organs Induced by Tumor Extracellular Vesicles - Dong, Qi; Liu, Xue; Cheng, Ke; Sheng, Jiahao; Kong, Jing; Liu, Tingjiao (Frontiers in Cell and Developmental Biology, 2021)
Primary tumors selectively modify the microenvironment of distant organs such as the lung, liver, brain, bone marrow, and lymph nodes to facilitate metastasis. This supportive metastatic microenvironment in distant organs was termed the pre-metastatic niche (PMN) that is characterized by increased vascular permeability, ECM remodeling, BMDC recruitment, angiogenesis, and immunosuppression. Extracellular vesicles (EVs) are a group of cell-derived membranous structures that carry various functional molecules. EVs play a critical role in PMN formation by delivering their cargos to recipient cells in target organs. We provide an overview of the characteristics of the PMN in different organs promoted by cancer EVs and the underlying mechanisms in this review.